DESIGNING A COMPACT FIREFIGHTING VEHICLE FOR NARROW RESIDENTIAL AREAS ON THE BASE OF A LAWN MOWER - Thong Duc HONG; Phat Tan TRUONG; Minh Quang PHAM; Lam Quang TRAN (Scientific Journal of Silesian University of Technology. Series Transport)
With the explosion of urbanization, more and more small residential areas with high population density, tiny houses, and narrow roads are formed. As a result, it is challenging for large fire engines to penetrate these areas in the event of a fire incident. In this paper, a compact firefighting vehicle was designed based on the SNAPPER LT140H331KV lawn mower. The vehicle is equipped with a water sprayer system and a folding frame water tank. The water sprayer system transmits power from the lawn mower transmission’s power take-off shaft via the belt and chain drive, which can spray water at a height of about 13 m with a flow rate of 38 L/min. The 500-liter folding frame water tank has a rectangular shape that can be folded and dragged as a trailer. The water sprayer system and folding frame water tank not only have a simple, compact structure but also do not affect the lawn mowing function. This fire truck has a maximum speed of about 15 km/h and can move in a minimal road width of only 1.3 m, which is accommodation for residential areas within a 1÷2 km radius with narrow roads, high density of population and houses in least developed and developing countries (e.g., Vietnam, Laos, Cambodia), where the normal fire engines are difficult to access in time. Besides, the vehicle can be used for watering and spraying pesticides on gardens and small premises. The study has proposed a valuable solution to take advantage of vehicle functions to improve their convenience and usefulness.